Cannabis use in adolescence: case report - Maia, Bruno Santos (2017)
Introduction: The illicit use of drugs has increased among adolescents. These are a risk group and cannabis is the drug preferentially used. Drug abuse is a clinical indication for family assessment. The aim is to alert illicit drug use in adolescence and emphasize the importance of family assessment and brief intervention by the family doctor. Case description: A 18-year-old adolescent male, belonging to a nuclear family at stage V of the Duvall cycle and middle social class, living with his parents with deafness and a 14-year-old sister. Family history of alcoholism. Initiated cannabis use at age 16 and regular use motivated school failure. In April 2015 with complaints of irritability and loss of motivation, associated with lack of concentration. Complaints were justified by the revolt in relation to deaf parents. In Family Circle, the adolescent put his sister in the center of the family and parents apart. According to the Family APGAR, it was a family with moderate dysfunction. It was decided not to intervene with family because it was not considered a high-risk situation and to not go against the adolescent will. Advice was provided to drug abuse, adapted to the stage of change. In September 2015 stopped using cannabis, remaining abstinent in March 2016 and more motivated at school. The maintenance of abstinence and prevention of relapse were promoted. Comment: The family continues to be the most consistent social support. The family dynamics can be prejudiced when parents, especially deaf, deal with the problems of adolescents, increasing the risk of illicit drug use. The family assessment and evaluation of the motivation for change by the family doctor are essential because only in this way is possible to improve doctor-patient relationship and chances of therapeutic success.